2002
DOI: 10.1007/s00122-002-1056-4
|View full text |Cite
|
Sign up to set email alerts
|

Sequence variation in the gene encoding the 10-kDa prolamin in Oryza (Poaceae). I. Phylogenetic Implications

Abstract: Oryza L. (Poaceae) contains approximately 20 wild and two domesticated species and nine genomes. Major disagreements exist on its systematics and genome evolution. Sequence polymorphism in the gene that encodes the 10-kDa prolamin polypeptide (a seed storage protein) was used to determine phylogenetic relationships and evaluate current systematics for 19 Oryza species. This gene in Oryza is approximately 402-bp long, and includes a 72-bp signal peptide region. A strict consensus tree shows Oryza brachyantha (F… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
14
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 24 publications
(30 reference statements)
0
14
0
Order By: Relevance
“…There is inconsistency of topology in previous reports, monophyletic or paraphyletic (Wang et al, 1992;Aggarwal et al, 1999;Ge et al, 1999;Joshi et al, 2000;Nishikawa et al, 2005). The position of the FF genome varies greatly among studies, ranging from the most basal site of the genus to inside newly diverged species clusters (Wang et al, 1992;Ge et al, 1999;Joshi et al, 2000;Mullins and Hilu, 2002;Nishikawa et al, 2005). Wang et al (1992) reported EE genome species to be clustered with other O. officinalis complex species, but later studies reported that the EE genome branched before the diversification of AA, BB, CC and CCDD genome species (Ge et al, 1999;Zou et al, 2008).…”
Section: Introductionmentioning
confidence: 89%
See 2 more Smart Citations
“…There is inconsistency of topology in previous reports, monophyletic or paraphyletic (Wang et al, 1992;Aggarwal et al, 1999;Ge et al, 1999;Joshi et al, 2000;Nishikawa et al, 2005). The position of the FF genome varies greatly among studies, ranging from the most basal site of the genus to inside newly diverged species clusters (Wang et al, 1992;Ge et al, 1999;Joshi et al, 2000;Mullins and Hilu, 2002;Nishikawa et al, 2005). Wang et al (1992) reported EE genome species to be clustered with other O. officinalis complex species, but later studies reported that the EE genome branched before the diversification of AA, BB, CC and CCDD genome species (Ge et al, 1999;Zou et al, 2008).…”
Section: Introductionmentioning
confidence: 89%
“…Wang et al (1992) reported EE genome species to be clustered with other O. officinalis complex species, but later studies reported that the EE genome branched before the diversification of AA, BB, CC and CCDD genome species (Ge et al, 1999;Zou et al, 2008). Other studies could not resolve the evolutionary pattern of EE and its close species with statistical significance (Joshi et al, 2000;Mullins and Hilu, 2002;Nishikawa et al, 2005).…”
Section: Introductionmentioning
confidence: 90%
See 1 more Smart Citation
“…Rice has all major TE types found in other plants, including retrotransposons, MITEs and other DNA elements (Bureau et al 1996;Mao et al 2000;Tarchini et al 2000;Mullins and Hilu 2002;Feschotte et al 2003;IRGSP 2005). Each type can be identified by its terminal sequences, its transposase and its target site duplication.…”
Section: Estimated Divergence Of O Brachyantha and O Sativamentioning
confidence: 95%
“…Oryza brachyantha, an FF genome-type grown mainly in dry regions of Central Africa, is evolutionarily distant to AA genome species (Mullins and Hilu 2002;Nishikawa et al 2005). O. brachyantha has the smallest genome within the Oryza genus, based on the c-value of nuclear DNA; it is~346-362 Mbp/1C compared to the~438 Mb/ 1C of cultivated rice -although actual genome size (~389 Mb) based on O. sativa sequence is smaller (Uozu et al 1997;IRGSP 2005;Ammiraju et al 2006).…”
mentioning
confidence: 99%